PEMANFAATAN SOSIAL MEDIA SEBAGAI SARANA PEMBELAJARAN DI ERA DIGITAL - Miftachul Aprilizdihar; Enjelya Dewi Pitaloka; Septiana Dewi (Pusat Penelitian dan Pengabdian Masyarakat, Politeknik Negeri Batam, 2021)
Advancing technological developments brought many useful platforms to the community, one of them is a learning platform. The purpose of this journal is to analyze how the academic students used and utilized social media by examining and analyzing various reference journals that other researchers have already studied and seeing how social media use is being used. And what we can see is that social media is very beneficial for college students because it has benefits such as looking for other references other than what the professor is giving. Moreover, it can help improve critical thinking ability. Social media is good not only for college students but also for everyone in the community.